2005
DOI: 10.1080/09593332608618607
|View full text |Cite
|
Sign up to set email alerts
|

Competitive and Hindering Effects of Natural Organic Matter on the Adsorption of MTBE onto Activated Carbons and Zeolites

Abstract: Equilibrium and kinetic adsorption of methyl tert-butyl ether (MTBE) onto three coal-based activated carbons, one coconut-based activated carbon, and two zeolites are elucidated in this study. Natural organic matter (NOM) and MTBE competed for the adsorption of activated carbons to different extents. The ideal adsorbed solution theory (IAST) combined with the equivalent background compound (EBC) model can adequately describe the NOM competition and predict the isotherms of MTBE onto the activated carbons. No c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
3
6
4
Order By: Relevance
“…These results indicate that the adsorption of DCM and MTBE on GACs was multilayer adsorption. The results were in good agreement with the results reported elsewhere (Hung et al, 2005).…”
Section: ) M)supporting
confidence: 93%
“…These results indicate that the adsorption of DCM and MTBE on GACs was multilayer adsorption. The results were in good agreement with the results reported elsewhere (Hung et al, 2005).…”
Section: ) M)supporting
confidence: 93%
“…The GACs derived from pecan and almond shells have been successfully tested for the removal of DCM (Bansode et al, 2003). Hung and coworkers had reported adsorptive removal of MTBE onto GAC derived from coconut shell (Hung et al, 2005). These studies motivated us to test and compare the feasibility of two commercially available GACs i.e.…”
mentioning
confidence: 99%
“…5. For comparison, the figure also includes the experimental data of MTBE in deionized water, STL groundwater and DG River water from the study of Hung et al [30]. The results revealed that the experimental data in natural waters for different initial concentrations were nearly identical with the solid line, the single-solute Freundlich isotherm, indicating that NOM did not compete with MTBE for the adsorption sites.…”
Section: Adsorption Isotherms Of Mordenite In Natural Watersmentioning
confidence: 63%
“…For comparison, Fig. 7 also includes the experimental data of MTBE in deionized water and STL groundwater from the study of Hung et al [30]. The Freundlich isotherm in deionized water was directly used in the model.…”
Section: Adsorption Kineticsmentioning
confidence: 99%